Semantic metrics. (14th July 2008) - Hu, Bo; Dasmahapatra, Srinandan; Lewis, Paul
In the context of the Semantic Web, many ontology-related operations, e.g., ontology ranking, segmentation, alignment, articulation, reuse, evaluation, etc., can be boiled down to one fundamental operation: computing the similarity and/or dissimilarity among ontological entities, and in some cases among ontologies. In this paper, we review conventional metrics for computing distance and we propose a series of metrics conceived purposely for semantics rich entities. We give a formal account of semantic metrics drawn from a variety of research disciplines and enrich them with formalisation based on Description Logics. We argue that concept-based metrics can be aggregated to produce numeric distances at ontology-level. We speculate on the usability of our ideas in potential ontology engineering tasks.